Taylor impact test revisited: Determination of plasticity parameters for metals at high strain rate. (1st June 2020) - Sen, Subhajit; Banerjee, Biswanath; Shaw, Amit
Abstract: Taylor impact test is the simplest experimental approach for characterizing plastic behaviour of metals under high strain rate (up to 10 5  s − 1 ). Herein, a cylindrical rod is impacted upon a rigid stationary anvil and the dynamic yield strength is estimated by comparing the experimentally obtained rod deformation with its theoretical counterpart. Despite being simple and potent concept, the lack of a comprehensive theoretical model (which relates the material constitutive with the deformation pattern of the rod) has so far restricted the use of the Taylor impact test in material characterization. In the present study the Taylor impact test is revisited and an attempt is made to formulate an inverse framework for efficient determination of constitutive parameters for metals. The inverse analysis is performed via the Extended Kalman Filter technique where the forward model is constituted based on the derivation given in Chakraborty et al. (2015). Unlike the common practice, for better estimation of material constants, the deformation time histories are also included in the present inverse formulation. For demonstration five different plasticity models viz Johnson–Cook model, Zerilli–Armstrong model, Steinberg–Cochran–Guinan–Lund model, Mechanical Threshold Stress model and Preston-Tonks-Wallace model are considered. The estimated parameters are found to be in good agreement with their reference values. It is shown that the most distinguished feature of the present attempt is that a single Taylor test is sufficient to determine the parameters with reasonable accuracy.